PERTUMBUHAN POPULASI Daphnia sp. YANG DIBERI LARUTAN DEDAK TERFERMENTASI MENGGUNAKAN RAGI TAPE - riana meilisa; yulisman .; ferdinand taqwa (Jurnal Akuakultur Rawa Indonesia, 2015)
ABSTRACT The purpose of this study were to know the effect of giving rice bran fermented using tape yeast for population growth ofÂ  Daphniasp. and to know the concentration of rice bran to increase populationsof Daphnia sp.. This study was conducted in the Laboratorium Dasar Perikanan, Aquaculture Program Study, Faculty of Agriculture, Sriwijaya University, Indralaya from July until September 2014. This study used randomized completely design method with five treatments and three replications. The treatment for culturing Daphnia sp. using chicken manure and rice bran fermented as feed. The treatments wereA (0.0005 g chicken manure.mL-1 culture media (control)), B (0.1 g.mL-1 rice bran fermented), C (0.15 g.mL-1 rice bran fermented), D (0.2 g.mL-1 rice bran fermented), E (0.25 g.mL-1 rice bran fermented). The parameters observed were the high population on firstcycle, the population growth, long Â time of the peak population Daphniasp. andphysics chemistry water. The result showed that fed rice bran fermented using tape yeast culture of Daphniasp. give effect to density, population growth, reached the long time population of Daphniasp. culture. The highest population density and growth rate in the culture of the Daphnia sp., using concentration 0.1 g.mL-1rice bran fermented. Keywords: Daphnia sp., rice bran, fermented, chicken manure, population growth